Identifying drivers for fishing pressure. A multidisciplinary study of trawl and sea snail fisheries in Samsun, Black Sea coast of Turkey - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
This study aims to investigate and model driving forces that lead to increased fishing pressure and an altered state of the environment in the coastal areas near Samsun on the Turkish Black Sea coast. We have applied a modified DPSIR model to structure our investigation and analysis and have investigated the drivers that generate fishing pressure in the Samsun fisheries. The overall health of the ecosystem is declining, and there is a consistent trend of deterioration in the condition of the three major species targeted by the trawl fisheries. Although introduced invasive species have brought significant changes to the Black Sea, it is clear that the state of the environment is significantly and negatively affected by the pressure exerted by fisheries. Fishing pressure has to a certain extent been redirected to pelagic trawling as bottom trawling has become less profitable and a rise in catch capacity has levelled off. This reduction is, however, offset by an increase in illegal trawling and dredging by a very rapidly growing sector of multi-purpose small boats, resulting in a considerable increase in the overall accumulated engine power of fishing boats in Samsun during 2000-2005. Fisheries in Samsun, in particular sea snail fisheries, have constituted a frontier of sorts open to the poorer populations of Samsun during the last 20 years, and, thereby, constitute one of the major drivers for fishing pressure. We identify eight drivers of importance for the period 2000-2005. Although the authorities can impact all or most of those drivers, most of them are beyond the scope of conventional 'fisheries management'. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: DPSIR APPROACH; MANAGEMENT; CATCHMENT